Striking the balance: Assertiveness training for constructive workplace conversations in India. - Jandhyala, Shivani; Kumar, Navin (Journal of Human Behavior in the Social Environment)
The Assertiveness Training Program seeks to cultivate a balanced and constructive approach to workplace communication, empowering participants with the skills needed to navigate conversations effectively. Recognizing the delicate equilibrium between Assertiveness and empathy, the program emphasizes the importance of expressing one's thoughts and needs assertively while fostering a collaborative and understanding atmosphere. An assessment is conducted for 50 employees on their Assertiveness Level and Leadership Competencies. The participants were asked to answer a questionnaire (Assertiveness and leadership competencies) before the beginning of the group training. Assertiveness. Tools: Rathus Assertiveness Schedule. Through a series of engaging workshops (8 Sessions) for employees with practical exercises, participants strike the right balance between Assertiveness and Active Listening, enabling them to communicate with confidence and receptivity. The program aims to equip individuals with tools to address conflict, provide constructive feedback, and build stronger professional relationships. By mastering the art of striking this balance, participants contribute to a workplace culture where open and respectful dialogue thrives, creating an environment conducive to innovation, teamwork, and overall organizational success.